Odpowiedzi

  • Użytkownik Zadane
2009-05-26T16:38:06+02:00
3y-6x-4=2x+2y+2
2x-6y+6=8y-6x-6

3y-6x-2x-2y=2+4
2x-6y-8y+6x=-6-6
y-8x=6 /+
8x-14y=-12 / + (dodajemy stronami)

y-8x+8x-14y=6-12
-13y=-6/ : (-13)
y ~0,46 ( w przybliżeniu)



2009-05-26T16:43:16+02:00
1 3[y-2x]=2[x+y]+2
3y-6x=2x+2y+2
y-8x=2
a co jest nie wiadomą w zadaniu..?

2 2[x-3y]+6=2[4y-3x]-6
2x-6y+6=8y-6x-6
8x-14y=0 rownanie tozasamościowe
Najlepsza Odpowiedź!
  • Użytkownik Zadane
2009-05-26T16:51:01+02:00
{3(y-2x)-4=2(x+y)+2
{2(x-3y)+6=2(4y-3x)-6

3y - 6x - 4 = 2x + 2y + 2
2x - 6y + 6 = 8y - 6x - 6

y - 8x = 6
8x - 14y = -12

-13y = -6
y = 6/13

8x = y - 6
8x = 6/13 - 6 = -72/13
x = -9/13


x = -9/13
y = 6/13